Tick-borne pathogens and their zoonotic potential for human infection In Thailand - Eamudomkarn, Chatanun (Veterinary Integrative Sciences, 2017)
Ticks are one of the important vectors for transmitting various types of pathogens in humans and animals, causing a wide range of diseases. There has been a rise in the emergence of tick-borne diseases in new regions and increased incidence in many endemic areas where they are considered to be a serious public health problem. Recently, evidence of tick-borne pathogens in Thailand has been reported. This review focuses on the types of tick-borne pathogens found in ticks, animals, and humans in Thailand, with emphasis on the zoonotic potential of tick-borne diseases, i.e. their transmission from animals to humans. Further studies and future research approaches on tick-borne pathogens in Thailand are also discussed